Climatic droplet keratopathy: An old disease in new clothes - Serra, Horacio Marcelo (2015)
Climatic droplet keratopathy (CDK) is an acquired and potentially handicapping cornea degenerative disease that is highly prevalent in certain rural communities around the world. It predominantly affects males over their forties. It has many other names such as Bietti's band-shaped nodular dystrophy, Labrador keratopathy, spheroidal degeneration, chronic actinic keratopathy, oil droplet degeneration, elastoid degeneration and keratinoid corneal degeneration. CDK is characterized by the haziness and opalescence of the cornea's most anterior layers which go through three stages with increasing severity. Globular deposits of different sizes may be histopathologically observed under the corneal epithelium by means of light and electron microscopy. The coalescence and increased volume of these spherules may cause the disruption of Bowman's membrane and the elevation and thinning of the corneal epithelium. The exact aetiology and pathogenesis of CDK are unknown, but they are possibly multifactorial. The only treatment in CDK advanced cases is a corneal transplantation, which in different impoverished regions of the world is not an available option. Many years ago, the clinical and histological aspects of this disease were described in several articles. This review highlights new scientific evidence of the expanding knowledge on CDK's pathogenesis which will open the prospect for new therapeutic interventions.